Cough symptom severity in patients with refractory or unexplained chronic cough: a systematic survey and conceptual framework. (14th July 2021) - Kum, Elena; Guyatt, Gordon H.; Devji, Tahira; Wang, Yuting; Bakaa, Layla; Lan, Lucy; Liu, Eva; Mastrolonardo, Alexander; Couban, Rachel; O'Byrne, Paul M.; Satia, Imran
Background: Cough severity represents an important subjective endpoint in assessing the effectiveness of therapies for patients with chronic cough. Although cough-specific quality of life questionnaires exist, a widely available cough severity instrument with established measurement properties remains unavailable. Aims: To identify and summarise the results of studies reporting on the experience of patients with chronic cough and, in the process, develop a conceptual framework to inform development of a patient-reported outcome measurement (PROM) addressing cough severity. Results: We identified 61 eligible studies reporting on patient experience with chronic cough. Studies provided 82 potential items, of which 43 proved unique and relevant to cough severity. The urge-to-cough sensation and the cough symptom itself represented broad domains of cough severity. Two subdomains under urge-to-cough included frequency (1 item) and intensity (1 item). Five subdomains under cough symptoms included control (2 items), frequency (6 items), bout duration (1 item), intensity (8 items), and associated features/sequelae (24 items). Conclusions: Our systematic survey and conceptual framework identified items and domains of cough severity in patients with refractory or unexplained chronic cough. The results support item generation and content validity for a PROM assessing cough severity. The urge-to-cough (frequency and intensity) and the cough symptom (control, frequency, bout duration, intensity and sequelae) represent domains to assess cough severity in patients with refractory or unexplained chronic cough https://bit.ly/3feqBXZ